Switching the light off: A break in photosynthesis and sap flow of forest trees under total solar eclipse - Karl-Heinz Häberle; Ilja Reiter; Katja Patzner; Christian Heyne; Rainer Matyssek (Meteorologische Zeitschrift, 2001)
In mature trees of Picea abies, Fagus sylvatica and Quercus robur, photosynthesis and transpiration were assessed in response to the total solar eclipse that occurred in Central Europe during the late morning hours of August 11, 1999, a day with changing cloudiness. Measurements were conducted at three forest sites located in the totality zone and the 99% area of the eclipse within a radius of about 100 km around the city of Munich (southern Germany). The eclipse lasting 164 minutes lowered the photosynthetic photon flux density (PPFD) to about 1 μmol m-2 s-1 during the 2-minute totality period, when the sky was clear. During totality, photosynthesis was reduced to an extent that allowed CO2 release to dominate the gas exchange of leaves. Effects on transpiration were less pronounced as the totality was apparently too short to induce distinct stomatal closure in response to low PPFD. Transpiration was strongly reduced, however, by increased air humidity and wet leaf surfaces during sporadic rain showers which preceded or succeeded the eclipse during the same day, whereas low PPFD through intermittent cloudiness during rain only moderately reduced photosynthesis. Although transpiration was lowered to a minor extent only by the eclipse, the latter affected the water transport through the whole tree, as reflected in a decline in the sap flow rate through the basal stem part with a time delay depending on the species. Nevertheless, trees responded in a synchronous way, regardless of the site, species or the percent degree of the eclipse.